Kheiron: A web application for pedagogical support focused on competitive programming training - de Oliveira, Lucas Santana (2024)
Competitive programming is a mental sport in which competitors solve Computer Science problems within a limited time without access to external materials. It gained popularity in primary and secondary education institutions with the growth of the internet and competitions such as the Brazilian Computer Olympiad and the Brazilian Programming Marathon. Teachers have trained their students to participate in these events, but the lack of suitable platforms makes it difficult to successfully prepare competitors. To meet this demand, the Kheiron web application was developed for pedagogical assistance, an application that facilitates the management and monitoring of students' studies by the teacher and provides analysis and content transfer tools, in addition to allowing the student to be served directly by the teacher/trainer or by a robot (bot) equipped with Generative Artificial Intelligence. To develop this work, exploratory research was carried out, followed by a bibliographic review.